2021
DOI: 10.3390/foods10040757
|View full text |Cite
|
Sign up to set email alerts
|

Durum Wheat (Triticum durum L.) Landraces Reveal Potential for the Improvement of Grain Carotenoid Esterification in Breeding Programs

Abstract: Carotenoids are essential in the human diet for their important functions in health. Besides, they are responsible for the yellow pigments desirable for industrial quality in durum wheat. The remarkable carotenoid content of durum wheat endosperm is mostly due to lutein. However, lutein esters have not been previously detected in durum wheat as in other cereals such as common wheat, tritordeum or Hordeum chilense. Esterification increases carotenoid stability and allows greater retention and accumulation throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 56 publications
3
21
0
Order By: Relevance
“…The MTAs for stem traits identified in this work that co-locate with previous QTLs can serve as a reference for the development of MAS strategies in wheat breeding. The diversity found in the plant material studied in this work highlights the potential of the plant genetic resources, as reported for other traits [11,12,14,39].…”
Section: Phenotypic Assessment Marker-trait Associations and Linkage Disequilibriumsupporting
confidence: 58%
See 1 more Smart Citation
“…The MTAs for stem traits identified in this work that co-locate with previous QTLs can serve as a reference for the development of MAS strategies in wheat breeding. The diversity found in the plant material studied in this work highlights the potential of the plant genetic resources, as reported for other traits [11,12,14,39].…”
Section: Phenotypic Assessment Marker-trait Associations and Linkage Disequilibriumsupporting
confidence: 58%
“…The Spanish durum wheat genetic resources are conserved at the Centre for Plant Genetic Resources (CRF-INIA). This collection has great genetic diversity for morphological, agronomic and quality traits [11][12][13][14]. Similarly, landraces from the Iberian Peninsula (Spain and Portugal) show greater diversity in relation to wheat stem sawfly (WSS, Cephus spp.…”
Section: Introductionmentioning
confidence: 99%
“…Carotenoids pigments are responsible for the bright yellow color of pasta and other durum wheat-derived products [ 4 ] and the golden color of related cereals such as tritordeum [ 5 ]. Lutein is the main carotenoid in wheat endosperm [ 4 , 5 ], but other carotenoids, including zeaxanthin, α-carotene and β-carotene, are also present [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies in recent years confirmed that lutein exists in both free and esterified forms in some wheat genotypes and other cereal grains (Paznocht et al, 2018;Requena-Ramírez et al, 2021). According to a recent report, lutein esters were detected in only 11 of 156 durum wheat genotypes (Requena-Ramírez et al, 2021), though they were more common in bread wheat and spelt wheat genotypes (Ziegler et al, 2015). Transition from free lutein to ester-linked lutein during long-term storage was also reported (Mellado-Ortega & Hornero-Méndez, 2017).…”
Section: Carotenoidsmentioning
confidence: 86%
“…Carotenoids in ester-linked forms with fatty acids (such as palmitic, stearic, oleic, and linolenic acids) were reported more than 50 years ago (Lepage & Sims, 1968). Studies in recent years confirmed that lutein exists in both free and esterified forms in some wheat genotypes and other cereal grains (Paznocht et al, 2018;Requena-Ramírez et al, 2021). According to a recent report, lutein esters were detected in only 11 of 156 durum wheat genotypes (Requena-Ramírez et al, 2021), though they were more common in bread wheat and spelt wheat genotypes (Ziegler et al, 2015).…”
Section: Carotenoidsmentioning
confidence: 98%